(3x-5)-(4x+7)=

Simple and best practice solution for (3x-5)-(4x+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-5)-(4x+7)= equation:


Simplifying
(3x + -5) + -1(4x + 7) = 0

Reorder the terms:
(-5 + 3x) + -1(4x + 7) = 0

Remove parenthesis around (-5 + 3x)
-5 + 3x + -1(4x + 7) = 0

Reorder the terms:
-5 + 3x + -1(7 + 4x) = 0
-5 + 3x + (7 * -1 + 4x * -1) = 0
-5 + 3x + (-7 + -4x) = 0

Reorder the terms:
-5 + -7 + 3x + -4x = 0

Combine like terms: -5 + -7 = -12
-12 + 3x + -4x = 0

Combine like terms: 3x + -4x = -1x
-12 + -1x = 0

Solving
-12 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -1x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + -1x = 0 + 12
-1x = 0 + 12

Combine like terms: 0 + 12 = 12
-1x = 12

Divide each side by '-1'.
x = -12

Simplifying
x = -12

See similar equations:

| -2+(-2)+(-2)+(-2)= | | 10+x=-7x+18 | | 4x^6-6x^5+14x^5-252x^4= | | 4w+3w+4w+3w=24 | | x+3y=180 | | 10x^2-23x-7=0 | | a=24-7(3) | | 5x+3-2x=0 | | 2x+4-x=3x-1 | | 3y+5=4y-12 | | x^2+.5x-3=0 | | 3(c-4)= | | G(x)=2x^2+6x+11 | | 3y+5=4y+12 | | 4w+3w+4w+3w= | | 3x-2(2x-5)=4 | | 4-20=-4 | | (x+16)/3=3x | | 5timesx-18-4timesx=-36 | | 6x+252=15x-9 | | 4+5x=3x-18 | | 2x-20=x-6 | | 3+4x=3x-1 | | 2.6=0.3x+0.4x | | 6(8x-5)=12x | | m+9=-21 | | 7t+5=0 | | x(x+0.89)=92.99 | | 2(f+7)-8=28 | | 1x+2=1x+2 | | 16t^2-110t=0 | | n+13=17 |

Equations solver categories